2010 Symposium on VLSI Technology 2010
DOI: 10.1109/vlsit.2010.5556234
|View full text |Cite
|
Sign up to set email alerts
|

World's first monolithic 3D-FPGA with TFT SRAM over 90nm 9 layer Cu CMOS

Abstract: World's first monolithically integrated Thin-Film-Transistor (TFT) SRAM configuration circuits over 90nm 9 layers of Cu interconnect CMOS is successfully fabricated at 300mm LSI mass production line for 3-dimensional Field Programmable Gate Arrays (3D-FPGA). This novel technology built over the 9 th layer of Cu metal features aggressively scaled amorphous Si TFT having 180nm transistor gate length, 20nm gate oxide, fully silicided gate, S/D, all below 400C processing essential to not impact underlying Cu inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…In 2010, Naito et al [85] showed a monolithic 3-D FPGA in which the a-Si TFT-based SRAM configuration memory was stacked over the CMOS logic and routing circuits. The memory cell used nine transistors, unlike conventional bulk SRAM cells with six transistors; the three additional TFTs were used as a buffer to isolate the cell's storage node from the bitline for the read operation.…”
Section: B Implementationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Naito et al [85] showed a monolithic 3-D FPGA in which the a-Si TFT-based SRAM configuration memory was stacked over the CMOS logic and routing circuits. The memory cell used nine transistors, unlike conventional bulk SRAM cells with six transistors; the three additional TFTs were used as a buffer to isolate the cell's storage node from the bitline for the read operation.…”
Section: B Implementationsmentioning
confidence: 99%
“…Cross-sectional SEM images of 3-D FPGA prototype chips: (a) nine-metal-layer CMOS logic circuits and a-Si TFT configuration memory[85];…”
mentioning
confidence: 99%
“…This is because FPGA devices typically have regular and highly-scalable structures, as well as stringent demands on high performance and energy efficiency. For example, FPGAs that use a 22-nm high-k/metal gate process technology and operate with frequencies up to 1.5 GHz have been announced [7]. Unfortunately, CMOS technology scaling also poses several technical challenges to FPGA device's reliability.…”
Section: Introductionmentioning
confidence: 99%
“…One promising way is 3D monolithic integration (3DMI), which can be broadly classified into two groups: a) active layer formation on a single wafer [1]- [6] and b) sequential stacking based on active layer transfer technology [7] [8]. Batude et al published their 3DIC researches based on molecular bonding technique with SOI wafer, Naito et al demonstrated 3D-FPGA with TFT SRAM, and low temperature poly-Ge CMOS technology was realized by Park et al As compared to TSV based 3D technology, the 3DMI technology can provide a low leakage current devices and a shortest wiring length for circuit design.…”
Section: Introductionmentioning
confidence: 99%